Patient-centered medicine transforming the clinical method - Stewart, Moira (Patient-centered care series, 2014)
It describes and explains the patient-centered model examining and evaluating qualitative and quantitative research. It comprehensively covers the evolution and the six interactive components of the patient-centered clinical method, taking the reader through the relationships between the patient and doctor and the patient and clinician. All the editors are professors in the Department of Family Medicine at the University of Western Ontario, London, Canada